Target DNA structure plays a critical role in RAG transposition. - Jennifer E Posey; Malgorzata J Pytlos; Richard R Sinden; David B Roth (PLoS Biology, 2006)
Antigen receptor gene rearrangements are initiated by the RAG1/2 protein complex, which recognizes specific DNA sequences termed RSS (recombination signal sequences). The RAG recombinase can also catalyze transposition: integration of a DNA segment bounded by RSS into an unrelated DNA target. For reasons that remain poorly understood, such events occur readily in vitro, but are rarely detected in vivo. Previous work showed that non-B DNA structures, particularly hairpins, stimulate transposition. Here we show that the sequence of the four nucleotides at a hairpin tip modulates transposition efficiency over a surprisingly wide (>100-fold) range. Some hairpin targets stimulate extraordinarily efficient transposition (up to 15%); one serves as a potent and specific transposition inhibitor, blocking capture of targets and destabilizing preformed target capture complexes. These findings suggest novel regulatory possibilities and may provide insight into the activities of other transposases.